Relationship between resting heart rate variability and intermittent endurance performance in novice soccer players - Pereira, L.; Abad, C. C. C.; Leiva, D.; Oliveira, G.; Carmo, E.; Kobal, R.; Loturco, I. (Research Quarterly for Exercise and Sport, 2019)
Purpose: This study examined the relationships between the Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1) and resting heart rate variability (HRV) and submaximal 5'-5' test derived measures in novice male soccer players. Methods: Forty players (11.54 ± 0.58 years) from a soccer academy participated in this study, performing physical tests on two different days, separated by 48 h, as follows: (day 1) resting HRV and Yo-Yo IR1 test, and (day 2) anthropometric assessments (for peak height velocity assessment [PHV]) and the 5'-5' test. The Pearson product-moment correlation coefficient was used to determine the correlations between Yo-Yo IR1 performance and the remaining variables. A partial correlation analysis was further performed using age, stature, body mass, distance to PHV, and age at PHV as "confounders." Results: The highest correlation score was observed between Yo-Yo IR1 performance and resting HRV, when the absolute age was used as confounder (r = 0.72; p < .05). Conclusions: We observed that a practical measure of parasympathetic activity at rest is largely associated with performance obtained during a traditional intermittent endurance performance test.